Large Enhancement of Carrier Transport in Solution‐Processed Field‐Effect Transistors by Fluorinated Dielectric Engineering. Issue 3 (25th November 2015) - Khim, Dongyoon; Xu, Yong; Baeg, Kang‐Jun; Kang, Minji; Park, Won‐Tae; Lee, Seung‐Hoon; Kim, In‐Bok; Kim, Juhwan; Kim, Dong‐Yu; Liu, Chuan; Noh, Yong‐Young
Abstract : The universal role of high‐ k fluorinated dielectrics in assisting the carrier transport in transistors for a broad range of printable semiconductors is explored. These results present general rules for how to design dielectric materials and achieve devices with a high carrier concentration, low disorder, reliable operation, and robust properties.